Legal Analysis of Civil Servant Neutrality in General Elections - Emilza Mumtaz; Berlianti Wahyu Nur Fatimah; Yahya Al Farisi; Titi Sari; Amelinda Cindy Laksintya; Arief Budiono (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Civil servant neutrality constitutes a fundamental principle in ensuring the integrity and fairness of democratic elections, particularly within administrative systems vulnerable to political influence. In Indonesia, despite the existence of a comprehensive legal framework regulating neutrality, persistent violations indicate a gap between normative provisions and practical enforcement. This study aims to analyze the legal regulation of civil servant neutrality in general elections and examine the effectiveness of sanction enforcement mechanisms. The research employs a qualitative juridical-normative method, utilizing statutory, conceptual, and comparative approaches based on primary legal materials and relevant scholarly works. The findings reveal that neutrality is firmly established through a hierarchical legal structure, including constitutional provisions, statutory laws, and implementing regulations; however, its enforcement remains inconsistent due to institutional fragmentation, interpretative ambiguities, and socio-political pressures. The analysis further demonstrates that weak coordination among supervisory bodies and varying sanction applications undermine legal certainty and deterrence. Therefore, strengthening neutrality requires regulatory harmonization, institutional reform, and the development of a professional bureaucratic culture grounded in integrity and accountability.